(untitled) (Journal of the College of Basic Education, 2022)
One of the modern training methods is the use of functional exercises that help the individual athlete to perform many movements in a skillful manner and depends on the athlete’s ability to perform many diverse sports activities naturally so that he can reach the highest levels of sports skills.One of the games that has received great attention in recent times is volleyball, which is one of the most popular games in the world. Volleyball requires great muscular ability to perform its skills, and when we look into the nature of performance, we find that it requires high energy to perform the motor duty with strength, speed and endurance. , as it requires from the players when performing its skills high physical and skill capabilities, and since the relationship between the basic skills of the game of volleyball and its various physical requirements is a close relationship that must be taken into account when preparing the players, and that there is no separation between the skill and physical preparations, but on the contrary, it must The physical elements are developed in accordance with the skill requirements, this achieves success in the training process, and then raises the level of the players. Airplane These exercises are characterized by intensity and short period of time and depend on tactical exercises accompanying them during physical and skill performance in general. Matching it is an integral part of the performance and thus we increase the ability of the volleyball player as a result of being exposed to more than one match in one week, especially during the gatherings of the qualifying matches or the league and thus this method of functional training. Since such training is closely compatible with the game of volleyball as we mentioned earlier, which requires physical preparation in line with the real mechanism of upgrading the players’ physical, skill and functional abilities, as the physical qualities are a reflection of the effort exerted, which in turn affects the raising of these capabilities, as the player must The high speed of the transition and the explosive power in jumping and the fluidity in the movement because the positions of the game change from one position to another and from one skill to another skill, and from this the research is gaining importance through the use of a modern training method in line with the development that is taking place, which is functional exercises through which the extent is revealed Its effect on the physical, skill and physiological abilities of advanced volleyball players.